Star-poly(lactide)-peptide hybrid networks as bioactive materials. (5th October 2020) - Arsenie, L.V.; Pinese, C.; Bethry, A.; Valot, L.; Verdie, P.; Nottelet, B.; Subra, G.; Darcos, V.; Garric, X.
Graphical abstract: Highlights: Synthesis and functionalization of tertrafunctionalized star PLA with IPTES groups. Creation PLA network by condensation of the silanol functions by a sol/gel route. Tunable mechanical properties of biomaterials to adapt them to the target tissue. The introduction of bioactive peptide strengthens the network and promotes cell. Abstract: Poly(lactide) (PLA) is a widely used biomaterial in many biomedical applications. However, it is inert and therefore lacks bioactivity, which is a major drawback in addressing tissue regeneration issues. This work aims to develop new implantable biomaterials composed of PLAs functionalized with bioactive peptides. For that purpose, we set up an original synthesis based on star-PLA bearing triethoxysilyl propyl groups (PLA-PTES) and bifunctional silylated peptides that react together via sol-gel process to create a bioactive network. We demonstrate that the molecular weight of the PLA and the quantity of peptide have a large influence on the crosslinking efficiency, the mechanical properties and the biodegradability of the resulting materials. The presence of peptide increases the crosslinking efficiency of the networks resulting in more rigid networks with stable mechanical properties up to 8 weeks. At last, the potential of this new type of hybrid biomaterials for soft tissue engineering was demonstrated through cells adhesion assays that showed a significant enhancement of fibroblasts adhesion.